Crescimento inicial e ecofisiologia de clones de eucalipto sob diferentes condições climáticas - Lopes, Tatiana da Silva (2009)
The objective of this study was to evaluate the growth and development of eucalyptus clones, analyzing the ecophysiology answers, in areas under different climatic conditions, in two periods of the year. The study of the behavior of eucalyptus clones in r